The Scientific Contributions of Bernard Cohen (1929–2019) - Maruta, Jun (Frontiers in Neurology, 2021)
Throughout Bernard Cohen’s active career at Mount Sinai that lasted over a half century, he was involved in research on vestibular control of the oculomotor, body postural, and autonomic systems in animals and humans, contributing to our understanding of such maladies as motion sickness, mal de débarquement syndrome, and orthostatic syncope. This review is an attempt to trace and connect Cohen’s varied research interests and his approaches to them. His influence was vast. His scientific contributions will continue to drive research directions for many years to come.